Strategic Self-Ignorance - Linda Thunström; Jonas Nordström; Jason F. Shogren; Mariah Ehmke; Klaas van 't Veld (Lund University, School of Economics and Management, Department of Economics, 2013)
We examine strategic self-ignorance—the use of ignorance as an excuse to over-indulge in pleasurable activities that may be harmful to one's future self. Our model shows that guilt aversion provides a behavioral rationale for present-biased agents to avoid information about negative future impacts of such activities. We then confront our model with data from an experiment using prepared, restaurant-style meals—a good that is transparent in immediate pleasure (taste) but non-transparent in future harm (calories). Our results support the notion that strategic self-ignorance matters: nearly three of five subjects (58 percent) chose to ignore free information on calorie content, leading at-risk subjects to consume significantly more calories. We also find evidence consistent with our model on the determinants of strategic self-ignorance.
Keywords: D03; D81; D83; 330; Experiment; Information; Ignorance